The current state of absence epilepsy: can we have your attention? - Tenney, Jeffrey R; Glauser, Tracy A (Epilepsy currents, 2013)
Absence seizures are common within many different epilepsies and span all the ages. Even though absence seizures were described more than three centuries ago advances associated with its classification, pathophysiology, genetics, treatment, prognosis, and associated co-morbidities continue to be made.